2020
DOI: 10.4000/geomorphologie.14411
|View full text |Cite
|
Sign up to set email alerts
|

Trajectoire d'évolution d'un cours d'eau à très faible énergie : le cas de la Charente entre Angoulême et Saintes (Ouest de la France)

Abstract: Articles sous presse Trajectoire d'évolution d'un cours d'eau à très faible énergie : le cas de la Charente entre

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(16 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…The fluvial pattern of the Charente River undergoes changes along its course. It starts as an irregular incised single channel from its source to Civray, transitions to a highly anastomosed pattern with 2-13 channels between Civray and Angoulême, becomes discontinuous and weakly anastomosed with 3-5 channels from Angoulême to Cognac, and finally takes on a meandering-to-sinuous single-channel form from Cognac to the estuary [34][35][36][37].…”
Section: Study Areamentioning
confidence: 99%
See 4 more Smart Citations
“…The fluvial pattern of the Charente River undergoes changes along its course. It starts as an irregular incised single channel from its source to Civray, transitions to a highly anastomosed pattern with 2-13 channels between Civray and Angoulême, becomes discontinuous and weakly anastomosed with 3-5 channels from Angoulême to Cognac, and finally takes on a meandering-to-sinuous single-channel form from Cognac to the estuary [34][35][36][37].…”
Section: Study Areamentioning
confidence: 99%
“…Field observations within the study area indicate a predominant fine suspended load and a limited bedload consisting mainly of sandy sediments, particularly upstream from Cognac. Duquesne et al [34,35] have shown that fluvial forms have very limited mobility in the medium term (around 150 years) due to the natural characteristics of the river such as its very low slope and flood flows with minimal morphogenic effects. Additionally, there is minimal change in the number of islands, except for those influenced by human activities [36].…”
Section: Study Areamentioning
confidence: 99%
See 3 more Smart Citations